Prevalence of active trachoma and associated factors among school age children in Debre Tabor Town, Northwest Ethiopia, 2019: a community based cross-sectional study - Alebachew Shimelash; Mekuriaw Alemayehu; Henok Dagne; Getenet Mihiretie; Yonas Lamore; Eniyew Tegegne; Lake Kumlachew (BMC, 2022)
Abstract Background Trachoma is an infectious eye disease caused by Chlamydial trachomatis. It is a major health problem in poor nations, notably in Sub-Saharan Africa. Despite the severity of the problem, there was a scarcity of data on trachoma prevalence and associated factors among school-aged children in Debre Tabor town following SAFE and MDA. Objectives The goal of this study was to determine the prevalence of active trachoma and its associated factors among school-aged children in Debre Tabor, Northwest Ethiopia, in 2019. Methods A community-based cross-sectional study was used among school-aged children. Structured interview questionnaires, an observational checklist, and a physical examination were used to collect data from study participants who were chosen using a systematic random sampling procedure. IBM SPSS 20 was used to enter data, which was then transferred to IBM SPSS 20 for bivariate and multivariable logistic regression analysis. Result A total of 394 children aged 5-15 had been screened and took part in the study, with 9.9% (95% CI: 6.9, 12.7) testing positive for active trachoma. Having an unimproved larine type (AOR = 5.18; 95%CI: 1.96, 13.69), improper solid waste disposal (AOR = 3.026; 95%CI: 1.17, 7.8), family size greater than four (AOR = 3.4; 95%CI: 1.22, 9.49), not using soap for face washing (AOR = 4.48; 95%CI: 1.46, 13.72) and an unclean face of the child during examination (AOR = 23.93; 95%CI: 8.25, 69.38) were found to be significant predictors of active trachoma. Conclusion Active trachoma among school-age children was high compared to the WHO's definition of trachoma as a public health problem. A family size of four, poor solid waste management, an unimproved type of latrine, an unclean child's face, and not using soap when washing one's face were all significant predictors of active trachoma. Promotion of behavioral determinants through health education programs like keeping facial cleanliness by washing their child's face with soap, managing solid waste properly, and installing improved latrines to reduce active trachoma needs to be in place.